Conteúdo, usabilidade e funcionalidade: três dimensões para a avaliação de portais estaduais de governo eletrônico na web - Renata Moutinho Vilella (2003)
Electronic Government is the theme of this work wich aims at creating an evaluation instrument and evaluating Brazilian States portals for public service delivery and dissemination of information in the Web. The work intended to verify if Brazilian States portals are utilizing, in fact, the potential of the Internet, if they are really becoming information and communication systems, making interactiveservices viable, promoting the exchange and sharing of information in cooperative environment. These functions are very distinct from only a static replacement of information. Three dimensions are analyzed in order to promote the evaluation of the Brazilian State portals as means to deliver public services and disseminate information on the Web: content, usability and functionality. For this purpose, an instrument of evaluation was built based on the existing literature and the opinion of specialists in each dimension of proposed analyses. The results obtained led us to conclude that, in fact, every single portal analyzed in this present work include one or more mechanisms to provide access to citizens about different fields of knowledge related to State governments. Therefore, theycan be considered as information systems. However, the State portals show great deficiencies as channels of communication, making viable communication in only one way (Government!Citizen), and do not provide the effective participation of the citizens. In addition, the work allowed us to clearly understand the problem of subjectivity in evaluation, so discussed by the authors that broach the information system evaluation theme. It is an undeniable fact, being clearly felt throughout the whole process of the present evaluation. The work furthermore allowed us to conclude that the State portals for public service delivery and dissemination of information in the Web need to constitute themselves a tool at citizens service, contributing to strengthen democratic life. TheseStates portals should take advantage of the possibilities the techonology provides, as it is known that the Internet is a media that allows a permanent process of learning, and offer the possibilities ofinterchange, communication and cooperation that characterize the informational society based on knowledge.